(untitled) (International Journal of Food and Nutritional Sciences, 2022)
E-commerce services are widely concentrated on customer service. This study has been undertaken to measure customer service by using customer perception variables toward E-commerce service. A parametric One-Sample T-test, the descriptive test is used to identify customers’ perception of various e-commerce services. In this study variables like ease of use, trustworthiness, relative advantage, cost-effectiveness, and customer satisfaction, influence customer perception among individuals. This research is specifically limited to the thane region and also limited to specific e-commerce apps like Amazon, Flipkart, Myntra, Nykaa, Purple, Meesho, Shopsy, Paytm, Google Pay, Phone PE, Bhim, Zomato, Swiggy, Uber, Ola, JioMart, Big Basket, Grofers, Tata Cliq, Rapido, Cred.